Identification and genetic diversity of Spodoptera frugiperda in Lampung Province, Indonesia - Puji Lestari; ADRIYANA BUDIARTI; Yuyun Fitriana; FX. SUSILO; I GEDE SWIBAWA; HAMIM SUDARSONO; RADIX SUHARJO; AGUS M. HARIRI; PURNOMO; NURYASIN; SOLIKHIN; LESTARI WIBOWO; JUMARI; MAMAN HARTAMAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lestari P, Budiarti A, Fitriana Y, Susilo FX, Swibawa IG, Sudarsono H, Suharjo R, Hariri AM, Purnomo, Nuryasin, Solikhin, Wibowo L, Jumari, Hartaman M. 2020. Identification and genetic diversity of Spodoptera frugiperda in Lampung Province, Indonesia. Biodiversitas 21: 1670-1677. Spodoptera frugiperda is one of the most recent invasive and destructive insect pest in Indonesia. Recently, it has been reported that this pest was found in some cornfield areas in Sumatera, including Lampung. This research was performed to confirm the presence of S. frugiperda in Lampung Province by collecting and identifying larvae of Spodoptera found in the field as well as investigation on the genetic diversity of the established populations and to observe the damage caused by this pest on cornfields in the Lampung Province. The observation was conducted from February-April 2019 at four locations (districts) representing corn-producing areas in Lampung, namely Lampung Selatan, Lampung Timur, Pesawaran and Pringsewu, each location comprising five plots. The plot is a cornfield with plants aged 14-40 days after planting. Twenty plants were randomly chosen in every plot as plant samples to collect the Spodoptera larvae and to calculate the absolute plant damage caused by the larvae. The absolute plant damage was analyzed by dividing the attacked plants with total plants observed and multiply by 100%. Identification of the Spodoptera larvae was performed based on morphological characters and molecular techniques using sequence analysis of Cytochrome c Oxidase subunit I (COI) gene. The result confirmed that the larvae found in the cornfield in Lampung were S. frugiperda. There was no nucleotides variation in the sequence of COI gene among S. frugiperda found in Lampung Province (Lampung Selatan, Lampung Timur, Pesawaran and Pringsewu) as well as S. frugiperda that was found in corn from foreign countries. The absolute plant damage caused by this pest in the four districts of Lampung was in the range of 26.50-70%.